Unveiling the Diverse Mammalian Species of a Tropical Rainforest in Northeast Bangladesh (Bangladesh Journal of Zoology, 2023)
Tropical rainforest supports an incredible diversity of mammalian species. The forest patches of northeast Bangladesh are considered hotspots for a range of threatened mammals. However, the transboundary Lathitila reserve forest in Moulvibazar district of northeast Bangladesh remained largely unexplored. We assessed the diversity of medium- and small-sized mammals using camera-trapping, and distance sampling, which was supplemented by sign survey and interviews. We recorded a total of 38 species of mammals belonging to 9 orders and 22 families. The Carnivora (34%) contained the highest number of mammals followed by Rodentia (21%), Primates (18%), Chiroptera (10%), and Artiodactyla (5%). Thirty seven percent of the recorded species were rare, followed by very common (26%), occasional (24%) and common (13%). Of these, 45% were categorized as threatened in the updated national Red List of IUCN Bangladesh. The remarkable species that we recorded are the Critically Endangered Asian elephant (Elephas maximus), Western hoolock gibbon (Hoolock hoolock), Chinese pangolin (Manis pentadactyla), Phayre’s leaf monkey (Trachypithecus phayrei), Northern pig-tailed macaque (Macaca leonina), and Bengal slow loris (Nycticebus bengalensis). The Endangered Fishing cat (Prionailurus viverrinus), and Asian small-clawed otter (Aonyx cinerea) were also recorded. The principal threats to the Lathitila forest are the habitat degradation, habitat fragmentation, human disturbance, illegal wood extraction, and wildlife poaching. This study highlights the conservation importance of this least-known forest, thereby protection measures are urgently needed to conserve its diverse mammalian fauna.Bangladesh J. Zool. 51(2): 135-154, 2023